Chiral inversion of R(-) fenoprofen and ketoprofen enantiomers in cats - Castro, Eduardo Fidel (2000)
The chiral inversion process is a characteristic metabolic pathway for different aryl-2-propionic acids or profens. Important variations have been observed between these individual compounds as well as between animal species. In this study, R(-) fenoprofen [R(-)FPF] and R(-) ketoprofen [R(-) KTF] were used to investigate their comparative stereoconversion in cats. After intravenous (i.v.) administration of R(-) FPF, the percentage of chiral inversion was 93.20±13.70%. A highly significant correlation (r: 0.978) was observed between the clearance of R(-) FPF and the chiral inversion process. After i.v. administration of R(-) KTF, the percentage of inversion was only 36.73±2.8%. No correlation between the clearance of R(-) KTF and this process was observed. R(-) FPF was metabolized by the pathways of thioesterification ? chiral inversion processes. For R(-) KTF, the competitive metabolic pathways, glucuronidation and hydroxylation may be involved. However, these metabolic steps are saturable or less functional in cats. Moreover, the thioesterification of R(-) KTF in in vitro studies has been shown to be important in carnivores. The lack of correlation between clearance and chiral inversion process of R(-) KTF may be finally explained by deviation of thioesterification to other metabolic pathways of lipids and/or aminoacid conjugation, particulary glicine derivatives.